PERAN PEMERINTAH DAERAH DALAM PENANGANAN KONFLIK PERTANAHAN DI KANTOR PERTANAHAN KABUPATEN LUWU TIMUR - Saenal, Saenal; Subair, Laola; Nur, Abdul Rahman; Salmi, Salmi; Kamal, Kasmad (PRAJA: Jurnal Ilmiah Pemerintahan, 2026)
Land conflicts are complex issues that frequently occur in various regions in Indonesia and impact the social, economic, and political stability of communities. Local governments play a crucial role in resolving land conflicts because they are closest to the community and have authority over regional management. This study aims to analyze the role of local governments in resolving land conflicts and identify obstacles encountered in their implementation. The research method used is a qualitative approach, collecting data through interviews, searching for relevant literature, and documenting relevant parties. The results indicate that local governments play a role in providing preventive and repressive legal protection in resolving land conflicts. However, this role is not yet optimal due to obstacles such as a lack of good faith from each party and the continued refusal of parties to implement peace agreements. Strengthening institutional capacity and increasing synergy between parties is needed to create a just, transparent, and sustainable resolution of land conflicts.